Conception, types and consequences of the invalid wills as to the current civil legislation of Ukraine - Сібільова, С. М. (Problems of legality, 2013)
In the article on the base of the analysis of the general norms on the invalidity of the transactions and special norms on the invalidity of the will and taking into account the main provisions of the long scientific discussion concerning the legal nature of the invalidity of the transactions, the doctrinal statement of the invalidity of the will has been proposed, the general characteristics of the types and legal consequences of the invalidity of the will has been exercised.